Construction and use of a Cupriavidus necator H16 soluble hydrogenase promoter (PSH) fusion to gfp (green fluorescent protein) - Jugder,Bat-Erdene; Welch,Jeffrey; Braidy,Nady; Marquis,Christopher P. (PeerJ, 2016)
Hydrogenases are metalloenzymes that reversibly catalyse the oxidation or production of molecular hydrogen (H2). Amongst a number of promising candidates for application in the oxidation of H2 is a soluble [Ni–Fe] uptake hydrogenase (SH) produced by Cupriavidus necator H16. In the present study, molecular characterisation of the SH operon, responsible for functional SH synthesis, was investigated by developing a green fluorescent protein (GFP) reporter system to characterise PSH promoter activity using several gene cloning approaches. A PSH promoter-gfp fusion was successfully constructed and inducible GFP expression driven by the PSH promoter under de-repressing conditions in heterotrophic growth media was demonstrated in the recombinant C. necator H16 cells. Here we report the first successful fluorescent reporter system to study PSH promoter activity in C. necator H16. The fusion construct allowed for the design of a simple screening assay to evaluate PSH activity. Furthermore, the constructed reporter system can serve as a model to develop a rapid fluorescent based reporter for subsequent small-scale process optimisation experiments for SH expression.
Keywords: Soluble hydrogenase; Ralstonia eutropha; Cupriavidus necator; Green fluorescent protein; Promoter